An Analysis Of Figurative Translation Techniques From Indonesian To English In The Novel “Gadis Kretek” At SMK N 6 Medan - Melinda Nababan; Kammer Tuahman Sipayung; Nurhayati Sitorus (Lembaga Riset dan Inovasi Almatani, 2026)
This author aims to analyze the figurative translation techniques applied by students in translating figurative expressions from Indonesian to English in the novel Gadis Kretek. The study employs a qualitative descriptive method to identify, classify, and describe the translation techniques used by the students. The data were obtained from the students’ translation works, focusing on various types of figurative language such as metaphor, simile, irony, hyperbole, metonymy, personification. The findings reveal that several translation techniques are dominantly used, including literal translation, equivalence, modulation, and adaptation. The results indicate that while literal translation is the most frequently applied technique, other strategies are also utilized depending on the contextual meaning of the figurative expressions. This study provides insights into how students manage the challenges of figurative language translation and contributes to the understanding of translation studies in an educational context.